Defects in the legal construction of fixed-term employment contracts in Polish labour law - Stelina, Jakub (The use of atypical forms of employment in violation of labour and social security laws - diagnosis and prospects for the future, 2023)
The author explains what the defects were in the legal construction of fixed-term employment contracts in Polish labour law. With the entry into force of the Labour Code in 1975, the principle was adopted that contracts of this type could be terminated earlier if the content of the contract provided for this possibility. This solution, after 1989, contributed to huge pathologies on the labour market related to the abuse of fixed-term contracts by employers. The legislator has repeatedly attempted to rectify this situation by, inter alia, introducing restrictions on the use of these contracts. These attempts were mostly ineffective, and the reason for the popularity of fixed-term contracts was that they could be unilaterally terminated. For incomprehensible reasons, in 2016 the legislator extended the possibility of such terminations and thus completely distorted the essence of the contracts in question.